Short Femur Is Not A Good Marker Of Down Syndrome In Peruvian Fetus - Limay-Ríos, Oscar Antonio (2017)
Objective. To determine the similarity or difference in femur length of normal fetuses compared to fetuses with Downsyndrome at the Maternal Perinatal Institute period 2011-2015. Methodology. It is a quantitative, retrospective, observational,descriptive and cross-sectional descriptive study. Our population was all fetuses of the National Perinatal Maternal Institutein the period 2011-2015, which had the measure of Femur Length and the complete database, which meet the criteria ofInclusion and Exclusion.